Analisis Kritis atas Sikap Rasional Berfaham Utility pada Konsumen Konvensional serta Penawaran Alternatif Sikap Rasional Islami Berfaham Maslahah pada Konsumen Muslim - Dwi Umardani (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractÂ This research is intended to find out the weaknesses of the rational attitudes of consumer based on utility in conventional economics and to offer the alternative solution to the Islamic rational attitudes of consumer based on maslahah in Islamic economics. The research method used is a qualitative method with primary and secondary data collected through literature review and analyzed in depth to clarify the cases being studied. After critical analysis, the rational attitudes of consumer based on utility in conventional economics turn out to be independent depending on each individual perception. Therefore, the rational attitudes based on utility must be perfected into the Islamic rational attitudes based on maslahah which is restricted-free with guidance of wahyu so that those can be applied to consumer activities in Islamic economics. Â Keywords: Rational attitudes, Islamic rational attitudes, utility, and maslahah.